Students’ Computational Thinking in Flat-Surfaced Solid Geometry: A Systematic Literature Review - Nisa Aula Nurussalamah; Cecep Anwar Hadi Firdos Santosa; Anwar Mutaqin; Novaliyosi (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
The integration of computational thinking (CT) has become increasingly essential in mathematics education, particularly in topics that require spatial reasoning and structured problem solving, such as flat-surfaced solid geometry. This study aims to synthesize empirical evidence on students’ computational thinking abilities within this specific mathematical context through a Systematic Literature Review (SLR). Using a descriptive qualitative approach, this review analyzed seven peer-reviewed articles published between 2020 and 2025 in nationally accredited journals indexed at SINTA levels 1–5. The literature search was conducted using Google Scholar and Publish or Perish, guided by predefined inclusion and exclusion criteria, and the study selection process followed PRISMA guidelines. The findings reveal that students’ computational thinking abilities are generally at low to moderate levels and unevenly developed across indicators, with abstraction and decomposition more prominent than pattern recognition and algorithmic thinking. Instructional designs incorporating visualization, contextualization, and structured problem engagement effectively supported CT development, whereas unplugged and manipulative-based activities proved beneficial at the elementary level. However, most studies emphasize outcome-based assessments and provide limited insight into students’ cognitive processes during problem solving. These findings highlight the need for theoretically grounded instructional designs and process-oriented assessment frameworks to support a more integrated and sustainable development of computational thinking in geometry learning.